PENGARUH PROJECT BASED LEARNING TERHADAP MOTIVASI BELAJAR DAN KEMAMPUAN BERNALAR KRITIS SISWA KELAS IV PADA MATA PELAJARAN IPAS DI KABUPATEN MAGELANG - Oktaviana; Wahyono, Hari; Zuhairi, Aminudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the effect of the Project Based Learning (PjBL) model on students’ learning motivation and critical thinking skills in fourth-grade Natural and Social Sciences (IPAS) classes in Magelang Regency. The study was motivated by the relatively low levels of students’ learning motivation and critical thinking skills in IPAS instruction, which has predominantly been conducted using conventional teaching methods. Therefore, a more active, contextual, and student-centered learning model was considered necessary. This research employed a quantitative approach using a quasi-experimental method with a non-equivalent control group design. The sample consisted of an experimental class taught using the PjBL model and a control class taught using conventional instruction. The research instruments included a learning motivation questionnaire and a critical thinking skills test, both of which had been tested for validity and reliability. The data were analyzed using MANOVA to determine the effect of the PjBL model on both dependent variables simultaneously and partially. The results indicated that the Project Based Learning model had a significant effect on students’ learning motivation and critical thinking skills, both partially and simultaneously. Thus, the implementation of PjBL was proven to be effective in improving the quality of IPAS learning in elementary schools and in strengthening students’ critical thinking skills and learning motivation.